Genome-Wide DNA Methylation Analysis in Male Methamphetamine Users With Different Addiction Qualities - Liu, Liang; Luo, Tao; Dong, Huixi; Zhang, Chenxi; Liu, Tieqiao; Zhang, Xiangyang; Hao, Wei (Frontiers in Psychiatry, 2020)
This paper aimed to explore the genome-wide DNA methylation status of methamphetamine (MA) abusers with different qualities to addiction and to identify differentially methylated candidate genes. A total of 207 male MA abusers with an MA abuse frequency of ≥10 times and an MA abuse duration of ≥1 year were assigned to the high MA addiction quality group (HMAQ group; 168 subjects who met the diagnostic criteria for MA dependence according to the DSM-IV) or to the low MA addictive quality group (LMAQ group; 39 subjects who did not meet the criteria for MA dependence). In addition 105 healthy controls were recruited. Eight HMAQ subjects, 8 LMAQ subjects and 8 healthy controls underwent genome-wide DNA methylation scans with an Infinium Human Methylation 450 array (Illumina). The differentially methylated region (DMR) data were entered into pathway analysis, and the differentially methylated position (DMP) data were screened for candidate genes and verified by MethyLight qPCR with all samples. Seven specific pathways with an abnormal methylation status were identified, including the circadian entrainment, cholinergic synapse, glutamatergic synapse, retrograde endocannabinoid signaling, GABAergic synapse, morphine addiction and PI3K-Akt signaling pathways. SLC1A6, BHLHB9, LYNX1, CAV2 and PCSK9 showed differences in their methylation levels in the three groups. Only the number of methylated copies of CAV2 was significantly higher in the LMAQ group than in the HMAQ group. Our findings suggest that the circadian entrainment pathway and the caveolin-2 gene may play key roles in MA addiction quality. Further studies on their functions and mechanisms will help us to better understand the pathogenesis of MA addiction and to explore new targets for drug intervention.